Performance of the FONT3 fast analogue intra-train beam-based feedback system at ATF - Burrows, P; Christian, G; Clarke, C; Dabiri Khah, H; Hartin, T; Perry, C; White, G; Kalinin, A; McCormick, D; Molloy, S; Ross, M (European Physical Society Accelerator Group (EPS-AG), 2006)
We report results of beam tests of the FONT3 intratrain position feedback system prototype at the Accelerator Test Facility (ATF) at KEK. The feedback system incorporates a novel beam position monitor (BPM) processor with latency below 5 nanoseconds, and a kicker driver amplifier with similar low latency. The 56 nanosecond-long bunchtrain in the ATF extraction line was used to test the prototype feedback system. The achieved latency of 23ns provides a demonstration of intra-train feedback on very short timescales relevant even for the CLIC Linear Collider design.